THE ROLE OF CLASSROOM TASKS IN DEDUCTIVE AND INDUCTIVE GRAMMAR INSTRUCTION - Kurbonova Iroda,; Orzikulova Mavsuma Mamatkulovna, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
The paper examines the role of classroom tasks in the process of the learning of grammar through deductive and inductive approaches to grammar instruction in ESL and EFL contexts. Specifically, it focuses on how different types of the classroom tasks contribute to  students'  grammatical development, cognitive  engagement and overall language acquisition. Most concepts relate to task structure, the degree of instructional sequencing, and the amount of teacher guidance. Comparing rule-oriented deductive tasks and discovery-oriented inductive tasks on accuracy, fluency, and metalinguistic awareness, the result shows deducing rules has advantages for explicit grammatical knowledge, rapid discovery of rules, and controlled practice, especially among lower skilled learners.  Inductive tasks, on the other hand, require  exploration, hypothesis generation  and  deep  processing  which  results  in  real  learning  and  information retention.  Based  on  the  findings,  the  paper  suggests  that  an  integrated  task-based approach which combines both deductive and inductive approaches should be adopted to better increase grammar learning. Therefore, the paper concludes by arguing that the appropriate  implementation  of  well-structured  classroom  tasks  is  pivotal  to maximizing  the  benefits  of  grammar  instruction, as  it  meets  the  needs  of  different learners  and  adopts  a  learner-centered  approach  as  well  as  promoting  explicit  and implicit learning